THE IMPORTANCE OF LISTENING IN FOREIGN LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2026)
This article examines the importance of using listening in foreign language teaching. Listening is the foundation of communication, and it is the beginning of mastering oral communication. Mastering this type of speech activity, such as listening, allows a person to understand what is being communicated and respond appropriately to what is being said, helping them formulate their responses correctly. When teaching listening, it is necessary to follow a specific sequence of exercises. Before listening to the text, exercises are usually performed that require differentiating new information, identifying the title, and recognizing individual elements.